Three weeks of mental training changes physiological outcomes during a time trial to exhaustion - VanHaitsma, T. A.; Gonzalez, S. P.; Kajitani, S.; Gabriano, E.; Hoiosen, G. E.; Oldach, M. C.; Kingsley, K. L. (European Journal of Applied Physiology, 2023)
Mental training (MT) can increase endurance performance. The purpose of this study was to examine the minimum dose of mental training needed to increase performance and elucidate the physiological mechanisms underlying this improvement. In a randomized between groups pre-test-post-test design, 33 participants visited the lab on 6 separate days. A VO2peak with ventilatory threshold (VT) was performed on day 1. The subsequent visits consisted of time trials to exhaustion (TTE) performed at 10% above VT. Between visit 3 and 6, the MT group (n = 16) watched a video for 10-15 min each day for 3 weeks, while the control group (CON; n = 17) did no mental training. Heart rate (HR), rate of perceived exertion (RPE), VAS scores for pain and fatigue, electromyography, and metabolic and neuromuscular data were collected and recorded during the time trials. The GRIT-S and CD-RISC 10 surveys were completed before study days 3 and 6. TTE increased significantly for MT beginning after 2 weeks (10.0 ± 13.1%) with no further change after 3 weeks (10.4 ± 13.2). TTE also significantly decreased during the last TTE for CON (-10.3 ± 12.7). VO2, ventilation, and frequency of breathing were significantly reduced in the latter stages of the TTE for MT. EMG was also significantly decreased for MT as compared for CON throughout the trial. Three weeks of mental training improves performance by reducing EMG, decreasing activation of the muscle and reducing metabolic factors during the latter stages of exercise.